Regulating Financial Conglomerates - Xavier Freixas; Gyöngyi Lóránth; Alan D. Morrison; Hyun Song Shin (National Bank of Belgium, 2004)
We analyse a model of financial intermediation in which intermediaries are subject to moral hazard and they do not invest socially optimally, because they ignore the systemic costs of failure and, in the case of banks, because they fail to account for risks which are assumed by the deposit insurance fund. Capital adequacy requirements are designed to minimise the social costs of these effects. We show that banks should always have higher regulatory capital requirements than insurance companies. Contrary to received wisdom, when banks and insurance companies combine to form financial conglomerates we show that it is socially optimal to separate their balance sheets. Moreover, the practice of "regulatory arbitrage", or of transfering assets from one balance sheet to another, is welfare increasing.
Keywords: 330; Finanzsektor; Konglomerat; Bank; Versicherung; Finanzintermediation; Betriebliche Liquidität; Theorie